EVALUATION OF THE FRICTION PAIR RESOURCE OF DISC-PAD BRAKES OF VEHICLES - Kindrachuk, Myroslav; Volchenko, Dmytro; Zhuravlev, Dmytro; Skrypnyk, Vasyl; Ihor; Lunin , Vasyl; Kharchenko, Volodymyr (Problems of Friction and Wear, 2023)
Theoretical and experimental studies of the energy load of a disc-pad brake of a vehicle made it possible to propose a method for determining the components of generated electric currents in metal-polymer friction pairs, based on experimental and calculated data, which is implemented in five stages, at each of which the total electric currents: thermal; the current that arises due to the friction of sliding and contact-interacting macro sections of the surfaces; current arising due to sliding friction, formed by the movement of charged mass transfer particles; the current caused by sorption-desorption processes in the near-surface layers of the lining, which are at a temperature higher than the permissible for its materials, as well as their direction. Determine the total wear during the braking cycle of the friction disc treadmill as the sum of losses due to its oxidation (corrosion) with the involvement of mechanical wear. The components (mechanical, electrical, thermal) of the friction power and their calculated values were determined with the help of the obtained dependencies. Based on the found value of the energy balance of the brake friction unit, the volume intensity of wear of the working surface of the lining was determined based on the obtained dependence with the transition to the dependence of the actual resource, taking into account the width and permissible thickness of the wear of the lining. The projected service life of the pad is achieved due to its working area and length, as well as the specified radius of the microprotrusions of the friction track of the disc. This method made it possible to increase the resource of the friction pad by 1.25 times under different operational parameters of the disc-pad brake of the vehicle.